The Family Education Role to Counter the Threat of Radicalism - Eka Hendry (AT-TURATS, 2020)
The existence of extremes religious groups continues to haunt and threat most countries in the world, including Indonesia. Although not monopolized by any particular religion, it is difficult to avoid the stigma that extremes of Islamist groups are still a scourge and in our social mindset. By the time, there is a transformation of the hard line movement starting from the form of organization, orientation of movement, target or target operations, recruitment model and the main issues that are propagated. This paper comes as an effort to unravel one of the dimensions of the transformation of the religious hardline movement, namely the recruitment process of hardline Islamic cadres. In this paper, radicalism is used to identify the doctrines instilled. One of the recruitment models is through the family's path. This phenomenon is actually not recently, because practices like these are already practiced. As example, among the executors of the WTC Bomb, there are several actors that are brothers. This article wants to explore the reasons why families become recruitment media, what issues play out in the process and what factors cause families to easily become recruitment media. At the end of this paper, the author tries to explain about the deradicalization efforts that need to be done in order to strengthen family immunity so as not to be easily exposed to radicalism. Keywords: Radicalism, Hardline Movement, family, Recruitment pattern, deradicalization, family immunity.